Physics - Cutnell, John D.; Johnson, Kenneth W. (John Wiley & Sons, Inc., 2007)
Helps readers understand the interrelationships among basic physics concepts and how they fit together to describe our physical world. This book also presents real world physics applications throughout the chapters, including many biomedical applications, to show how physics principles come into play over and over again in our lives.